2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6185997
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromatic aberration effects in triple-junction solar cells using advanced distributed models

Abstract: Abstract-The consideration of real operating conditions for the design and optimization of a multij unction solar cell receiverconcentrator assembly is indispensable. Such a requirement involves the need for suitable modeling and simulation tools in order to complement the experimental work and circumvent its wellknown burdens and restrictions. Three-dimensional distributed models have been demonstrated in the past to be a powerful choice for the analysis of distributed phenomena in single-and dual-junction so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…As for the perimeter region, an ideality factor of 2 was assumed for the diode model per subcell representing the edge recombination. [14][15][16][17][18]22 In Fig. 1, this is labeled as J 02p;i .…”
Section: Quasi-two-dimensional Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the perimeter region, an ideality factor of 2 was assumed for the diode model per subcell representing the edge recombination. [14][15][16][17][18]22 In Fig. 1, this is labeled as J 02p;i .…”
Section: Quasi-two-dimensional Simulation Modelmentioning
confidence: 99%
“…Good agreement of the measurements with the simulation model results suggests that the nonuniformity of the LC effect is optically induced. Moreover, it is less likely caused by edge recombination, which is typically modeled using electrical circuits alone [14][15][16][17][18] (see Appendix A.1). We have found that the absolute conversion efficiency reduction of the limiting cell due to nonuniform LC current generation is 1.35% at maximum LC efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…These spatial and spectral nonuniformities can cause current mismatch between the subcells in the MJ solar cell decreasing the cell current. For the case of high differences between irradiance profiles in the different subcells, the current spreading that depends on the lateral resistances of the cells (layers which make up the connection between two subcells ) can be the dominant factor of efficiency losses in high concentration systems (5,(9)(10)(11).…”
Section: Spatial and Spectral Non-uniform Light Distribution On Multimentioning
confidence: 99%
“…Current which has to be injected in darkness to emulate working conditions. For that simulations with our 3D distributed model for triple-junction solar cells have been carried out [5], [6]. The criterion followed has been that the absolute value of current density through the junctions in darkness does not surpass at any point of the solar cell the current density photo-generated in the active area at 820 X [4].…”
Section: Design Of the Testmentioning
confidence: 99%